Healthcare Education in Schools: A Curriculum Proposal Introduced Into Spanish Schools in the Name of Unchecked Development - Terrón Bañuelos, Aida (Education Policy Analysis Archives, 2015)
The article analyses the background to healthcare education in the Spanish school system. Spanish foreign policy and the fact that Spain became a member of a number of international organizations, such as the FAO and WHO (in 1951), UNESCO (1953), UN (1955), the International Monetary Fund and World Bank (1958) boosted the modernization of the economic, social and administrative fabric of the franquist regime, with a particularly perceptible effect on its education system. This process, which had been initiated in the sixties, reached its pinnacle with the General Education Act of 1970. Primary schooling, which had only been made compulsory in 1965, was conceived as a “social institution” whose role was to go hand in hand with the other major transformations taking place in the country. Healthcare education became one of the new educational domains, experts agreed, that were vital to the policies promoted by the aforementioned international organizations the country had now joined. This measure was implemented in the most disciplined manner by technocrats of the education administration, but quickly met with the obstacles and difficulties that will inevitably assail any imported process, resulting in strong resistance from within and without the school system, as it came to clash with the reality of the situation in the country.